(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This report was produced with the aim of sharing some reflections on the teaching proposal for the Shadow Theatre course, offered over two semesters in the Bachelor’s degree in Theatre from the State University of Santa Catarina, in the years 2023 and 2024. Specifically, it refers to research practices for the collective production of knowledge through the realization of a thematic seminar, focusing on traditional forms of shadow theatre, alongside reflections on the concept of contemporary shadow theatre and a panoramic observation of shadow theatre in Brazil. By addressing the specific objectives of the course, it seeks to broaden the students’ repertoire towards a counter-colonial perspective that considers other ways of being and existing in the world.